Capturing Business Strategy and Value in Enterprise Architecture to Support Portfolio Valuation - Iacob, M.; Quartel, D.; Jonkers, H. (2012 IEEE 16th International Enterprise Distributed Object Computing Conference, 2012)
This paper investigates and enhances the suitability of the Archi Mate enterprise architecture modeling language to support the modeling of business strategy concepts and architecture-based approaches to IT portfolio valuation. It gives an overview of existing strategy and valuation concepts and methods in the literature and motivates the need for enterprise architecture and business requirements modeling to capture these aspects as well. This overview results in the identification of strategy and value related concepts, such as value, risks, resources, capabilities, competencies and constraints. The paper provides an analysis of the extent to which Archi Mate may support some of the above-mentioned concepts and extends it with the missing concepts. The proposed language extension is formalized in terms of a met model fragment, which is aligned with the Archi Mate metamodel. The approach is also illustrated by means of an application portfolio consolidation case study in which we demonstrate how a constrained optimization valuation method can be applied to architecture models enhanced with the new concepts.